Impact of Gender Difference on Anxiety in COVID-19 Patients in Quarantine Wards - Sun, Peng; He, Tao; Fan, Duo-jiao; Xu, Chao; Wang, Ying; Song, Shuang-wei; Jin, Feng; Chen, Xiao-xue; Yang, Mei (Frontiers in Psychiatry, 2022)
Objective This study aimed to investigate the gender difference in anxiety in novel coronavirus pneumonia (COVID-19) patients in the quarantine ward during the outbreak. Methods The self-rating anxiety scale (SAS) was used on the seventh day of isolation to analyze the anxiety levels of a total of 242 suspected or confirmed COVID-19 patients in the quarantine wards of two hospitals; 232 of these patients (112 males and 120 females) completed the anxiety scoring. The anxiety scores were compared between male and female patients using the t-test, and a scatter diagram was used for analysis. Results The SAS scores of females in quarantine wards were higher than those of males at seven days of isolation. Conclusion Women with COVID-19 are more prone to anxiety than men while in isolation. It is necessary to give more attention to female patients in quarantine wards in the future, and psychological counseling may be necessary.